Metode Tafsir Lathaif Al-Isyarat Karya Imam Al-Qusyairi - Nida Amalia Kamal; Siti Madinatul Munawwaroh (Jurnal Iman dan Spiritualitas, 2021)
Al-Qur'an as a miracle is interpreted by the commentators using various methods, besides the general method, there is a special method used by each commentator in his interpretation. This study aims to examine the interpretation of Lathaif Al-Isunjuk by Al-Qusyairi and the specific method it uses in interpretation. From the results of the research that Al-Qusyairi is a Sufi who tries to interpret the verses of the Al-Quran with the application of the concept of Sufism, with an expressive literary language that brings the reader into a sense of the soul of Sufism This Sufi interpretation is an interpretation of the Al-Qur'an verse based on the spiritual experiences of the mufassir. Mufassir presents his interpretation according to the Sufi spirit so that the reader is carried away by the divine light in the soul of the Mufassir. Al-Qusyairi has a special method from other Sufi exegesis books, namely bayani isyari mu’jaz, the interpretation of the verses completely uses isyari, while other Sufi books combine isyari and language, it combines mind and soul and the interpretation is written briefly and clearly.